Importance of surgeon's experience in practicing valve-sparing aortic root replacementCentral MessagePerspective - Kavya Rajesh, BS; Megan Chung, BA; Dov Levine, MD; Elizabeth Norton, MD; Parth Patel, MD; Yu Hohri, MD, PhD; Chris He, BS; Paridhi Agarwal, BS; Yanling Zhao, MS, MPH; Pengchen Wang, MS; Paul Kurlansky, MD; Edward Chen, MD; et al. (JTCVS Open, 2024)
Background: Valve-sparing root replacement (VSRR) requires a unique skill set. This study aimed to examine the influence of surgeon's procedural volume on outcomes of VSRR. Methods: This retrospective study included 1697 patients from 2 large, high-volume aortic centers who underwent aortic root replacement (ARR) between 2004 and 2021 and were potentially eligible for VSRR. Surgeons were classified as performing <5 ARRs or ≥5 ARRs annually. Multivariable logistic regression was used to examine the independent association of surgeon volume and the decision to perform VSRR. Inverse probability treatment weighting (IPTW) was used to match patients who were operated on by <5 ARR surgeons or ≥5 ARR surgeons and compare long-term survival probability. Cumulative incidence curves with mortality as a competing risk were plotted to compare the rate of aortic valve reoperation. Results: Of 1697 patients who met the study inclusion criteria, 944 underwent composite-valve conduit ARR and 753 underwent VSRR. The median age of the cohort was 57 years (interquartile range, 45-66 years), and 268 (15.8%) were female. Aortic insufficiency was present in 1105 patients (65.1%), and 200 of the procedures (11.8%) were reoperations. The indication for surgery was aneurysm in 1496 patients (88.2%) and dissection in 201 (11.8%). Among the 743 patients who underwent VSRR, 691 (92%) were operated on by ≥ 5 ARR surgeons and 62 (8%) were operated on by <5 ARR surgeons. In multivariable logistic regression, ≥5 ARRs (odds ratio, 3.33; 95% confidence interval, 2.34-4.73; P < .001) was associated with VSRR as the procedure of choice. Following IPTW, there was no significant difference between <5 ARR and ≥5 ARR surgeons in survival probability after VSRR (P = .59) or in the rate of aortic valve reoperation (P = .60). Conclusions: In the setting of a high-volume aortic center, patients who undergo ARR are less likely to receive VSRR if operated on by a <5 ARR surgeon; however, VSRR may be safely performed by <5 ARR surgeons.